2014
DOI: 10.3109/00952990.2014.884102
|View full text |Cite
|
Sign up to set email alerts
|

Open-label pilot study of quetiapine treatment for cannabis dependence

Abstract: Background There are no efficacious pharmacotherapies for cannabis dependence. The effects of quetiapine are well matched to the symptoms of cannabis withdrawal and could be useful in the treatment of cannabis dependence. Objectives To evaluate quetiapine for the treatment of cannabis dependence and determine the optimal dosing. Methods In an eight-week open-label outpatient pilot trial, we evaluated the feasibility of quetiapine treatment for cannabis dependence in 15 outpatients. Quetiapine was gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…28 Other studies support this, identifying a three-fold increase in prescribing over a decade, 29 an observation likely driven by the increasing popularity of quetiapine use for “off-label” indications. 2 , 3 , 16 , 29 , 30 , 31 These prescribing patterns may contribute to why quetiapine is the most commonly abused SGA in terms of absolute numbers of cases.…”
Section: Discussionmentioning
confidence: 99%
“…28 Other studies support this, identifying a three-fold increase in prescribing over a decade, 29 an observation likely driven by the increasing popularity of quetiapine use for “off-label” indications. 2 , 3 , 16 , 29 , 30 , 31 These prescribing patterns may contribute to why quetiapine is the most commonly abused SGA in terms of absolute numbers of cases.…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the effect of lithium on cannabis use outcomes in an open-label trial and found improved abstinence outcomes and decreased symptoms of anxiety and depression [59]. Finally, another open label trial investigated the effects of the second generation antipsychotic quetiapine in cannabis-dependent individuals and found a significant decreased in urine THC levels [60]. Patients with co-occurring mood disorder diagnoses were not included in these open-label trials, so further research is warranted on the effects of these drugs on comorbid mood disorders with cannabis use.…”
Section: Methodsmentioning
confidence: 99%
“…This study involved non‐treatment seeking participants; however, authors felt this cannot explain the higher relapse among the Seroquel group. In contrast to Cooper's findings, a pilot open trial by Mariani et al showed treatment with Quetiapine was associated with a reduction in cannabis use among participants with Cannabis dependence. Therefore, the authors suggest to consider these findings preliminary until further research is available.…”
Section: Discussionmentioning
confidence: 57%